The Influence of Self-Directed Learning on Teacher Certification Success: Logistic Regression Analysis among Indonesian English Language Teachers - Triana Ramdha; Mirfaturiqa (Universitas Cokroaminoto Palopo, 2026)
This study investigated whether Self-Directed Learning (SDL), as viewed through the lens of Self-Determination Theory (SDT), predicts the chance of teacher professional certification (Pendidikan Profesi Guru, PPG) achievement among Indonesian English language teachers. Using a quantitative cross-sectional methodology, connected survey and certification records for 46 instructors selected purposively from Riau and nearby areas were examined using binary logistic regression. SDL was measured with a 15-item, three-dimensional instrument spanning autonomy, competence, and relatedness, which demonstrated excellent internal consistency in the current sample (α = .93). A confirmatory model tested total SDL score alongside teaching experience, while an exploratory model decomposed SDL into its three subscales. Total SDL score significantly predicted certification success after adjusting for teaching experience (OR = 1.12, 95% CI [1.01, 1.24]), with good model discrimination (AUC = .83) and adequate calibration (Hosmer-Lemeshow p = .49); teaching experience was the strongest single predictor (OR = 3.15). At the subscale level, only autonomy remained an independent, significant predictor (OR = 1.61, p = .036), while competence and relatedness did not reach significance once their shared variance was accounted for. These findings indicate that autonomy-supportive, self-initiated professional learning is the SDL dimension most worth prioritizing in PPG preparation and mentoring, while pointing to the need for larger, more complete datasets to confirm which dimensions matter most. The study contributes quantitative, probability-based evidence to a body of SDL-professional development literature that has so far relied largely on qualitative and continuous-outcome designs.